La difficile adaptation de la didactique convergente au contexte arabophone - Emna Souilah (Recherches en didactique des langues et des cultures)
This article deals with the accommodation of the integrated/convergent didactics to the Arabic context. It is a language teaching procedure devised in the north but which seems to bring up solutions to the French learning problems all over the world. Since it is built on the cognitive potential of the learner along with his mother tongue which is more likely to adaptation to different context. Hoping to remedy the teaching, the adaptation of this procedure has been carried out. This has led to the elaboration of a guide for training teachers of convergent didactics / French-Arabic. However on closer inspection of this guide, we discover that in order to face the difficulties pertaining to the particularity and the sociopsycholinguistic complexity of this context because of the Arabic language status and its variety, the adaptation work has led to a version of didactics at odds with the initial version.